2010
DOI: 10.1021/ol1018618
|View full text |Cite
|
Sign up to set email alerts
|

Verticilactam, a New Macrolactam Isolated from a Microbial Metabolite Fraction Library

Abstract: Systematic isolation of microbial metabolites has been performed to construct microbial metabolite libraries or fraction libraries. A novel macrolactam, verticilactam (1), was isolated from a library of Streptomyces spiroverticillatus JC-8444. The structure was determined on the basis of NMR and mass spectrometric measurements. 1 had a unique 16-membered macrolactam skeleton including a β-keto-amide moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The core structure of the macrotermycins ( 5 ) belongs to a family of macrolactam polyketides that include incednine, 10 vicenistatin, 11 silvalactam, 12 heronamides, 13 verticilactam, 14 ciromicins, 15 mirilactams and lobosamides. 16 Both 1 and 3 can be viewed as polyene precursors for intramolecular cycloadditions leading to 2 and 4 , respectively, and the relevant reaction pathways, whether enzymatically catalyzed or occurring spontaneously either in situ or during purification, are being investigated.…”
mentioning
confidence: 99%
“…The core structure of the macrotermycins ( 5 ) belongs to a family of macrolactam polyketides that include incednine, 10 vicenistatin, 11 silvalactam, 12 heronamides, 13 verticilactam, 14 ciromicins, 15 mirilactams and lobosamides. 16 Both 1 and 3 can be viewed as polyene precursors for intramolecular cycloadditions leading to 2 and 4 , respectively, and the relevant reaction pathways, whether enzymatically catalyzed or occurring spontaneously either in situ or during purification, are being investigated.…”
mentioning
confidence: 99%
“…To discover novel natural products that are normally expressed at a very low level, we have been performing a systematic isolation of secondary metabolites. As a result, we isolated verticilactam 4 from Streptomyces spiroverticillatus JC-8444, a tautomycin producer, 5 and 6-dimethylallylindole-3-carbaldehyde 6 from S. reveromyceticus SN-593, a reveromycin producer. 7 In addition, from S. reveromyceticus SN-593, we detected metabolites showing UV spectra similar to furaquinocin (FQ), but different mass from the reported FQs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we constructed a microbial metabolite fraction library by systematic separation with a spectral database, based on photodiode-array detector attached LC/MS analysis to discover structurally unique metabolites efficiently and rapidly. We discovered and isolated verticilactam 6 from S. spiroveticillatus JC-8444, a tautomycin producer, [7][8][9] and the new fraquinocins I and J 10 and 6-dimethylalylindole-3-carbaldehyde 11 from S. reveromyceticus SN-593, a reveromycin producer 12 by our methodology constructing the fraction library. Also, Bugni et al 13 reported a marine natural products library by HPLC-MS fractionation for rapid drug discovery.…”
Section: Introductionmentioning
confidence: 99%